2022
DOI: 10.1038/s41467-021-27750-2
|View full text |Cite
|
Sign up to set email alerts
|

Yeast-derived nanoparticles remodel the immunosuppressive microenvironment in tumor and tumor-draining lymph nodes to suppress tumor growth

Abstract: Microbe-based cancer immunotherapy has recently emerged as a hot topic for cancer treatment. However, serious limitations remain including infection associated side-effect and unsatisfactory outcomes in clinic trials. Here, we fabricate different sizes of nano-formulations derived from yeast cell wall (YCW NPs) by differential centrifugation. The induction of anticancer immunity of our formulations appears to inversely correlate with their size due to the ability to accumulate in tumor-draining lymph node (TDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 56 publications
1
48
0
Order By: Relevance
“…It is a promising cancer treatment method, with the advantages of cooperating two kinds of treatment mechanism ( Nowak and Lesterhuis, 2014 ). The very recent studies demonstrated that nanoparticles could remodel immunosuppressive tumor microenvironment, holding great promise for chemoimmunotherapy ( Xu et al, 2022 ). Moreover, nanobased delivery systems have exhibited excellent properties, such as targeted drug delivery, tumor microenvironment modulation, targeted and time-controlled release of conjugate drugs, so as to improve the pharmacokinetics and stability of drugs in vivo .…”
Section: Cancer Treatment: Prospects and Dilemmasmentioning
confidence: 99%
“…It is a promising cancer treatment method, with the advantages of cooperating two kinds of treatment mechanism ( Nowak and Lesterhuis, 2014 ). The very recent studies demonstrated that nanoparticles could remodel immunosuppressive tumor microenvironment, holding great promise for chemoimmunotherapy ( Xu et al, 2022 ). Moreover, nanobased delivery systems have exhibited excellent properties, such as targeted drug delivery, tumor microenvironment modulation, targeted and time-controlled release of conjugate drugs, so as to improve the pharmacokinetics and stability of drugs in vivo .…”
Section: Cancer Treatment: Prospects and Dilemmasmentioning
confidence: 99%
“…The combination of yeast-derived nanoparticles and PD-L1 antibody has shown a superior antitumor effect in CRC. It can not only effectively eliminate in situ tumor, but also inhibit the growth of distal spreading cancer cells [171].…”
Section: Modulation Of Gut Microbiota For Gi Cancermentioning
confidence: 99%
“…Microorganisms contain some compositions that are considered as PAMPs by immune system. Wang et al incubated yeast cells in NaOH at 80 °C for 1 h, followed by sonication and differential centrifugation to obtain EVs with different sizes [ 78 ]. These EVs contained ~ 88.2% β-glucan, 2.9% proteins and 8.9% other materials, and these activated DCs through Dectin-1/Syk and TLR2/MyD88 pathways.…”
Section: Applications Of Mps In Cancer Treatmentmentioning
confidence: 99%